Evaluation of forensic toxicological characteristics of cases under the age of eighteen with substance use: a sample from Türkiye - Kerem Sehlikoğlu; Murat Kamalak; Mehmet Dağlıoğlu; Seval Gülçiçek; Fatma Köse; Hicran Nermin Demir; Tuğba Çakır; Duygu Ülkü; Melek Rüveyda Koca; Demet Dönmez; Beyza Kılınç; Zeynep Bilge (The Turkish Journal of Pediatrics, 2025)
Background. Substance use is rapidly increasing in the pediatric age group worldwide. There is not enough toxicological data on substance use among children and adolescents in Türkiye. This study aims to reveal the forensic toxicological characteristics of cases under the age of eighteen with substance use detected.